NDO-BSA, LID-1, and NDO-LID Antibody Responses for Infection and RLEP by Quantitative PCR as a Confirmatory Test for Early Leprosy Diagnosis - Gobbo, Angélica Rita; Bouth, Raquel Carvalho; Moraes, Tania Mara Pires; Pinto, Pablo; da Costa, Patricia Fagundes; Barreto, Josafá Gonçalves; Frade, Marco Andrey Cipriani; Ribeiro-dos-Santos, Ândrea Kely; Conde, Guilherme Augusto de Barros; Duthie, Malcolm S.; da Silva, Moises Batista; Spencer, John Stewart; et al. (Frontiers in Tropical Diseases, 2022)
Diagnostic tests for leprosy are limited, especially to identify early leprosy cases. We performed active case findings of leprosy to validate three potential antigen candidates and one molecular target. Cases were diagnosed by characteristic skin lesions, nerve enlargement, or skin sensation loss. Serum samples obtained from all subjects were tested by ELISA to assess antibody titers to three Mycobacterium leprae specific antigens: NDO-BSA, LID-1, and NDO-LID. Most of the field cases on Mosqueiro Island, northern Brazil, also collected slit skin smear for qPCR. Active case finding diagnosed 105 new cases of leprosy out of 894 subjects (11.7%), revealing a high prevalence of M. leprae in the region. With the use of amplification of the M. leprae-specific RLEP by qPCR, 68/79 (86.07%) of these cases were positive, confirming leprosy in subjects diagnosed in the field. Patients diagnosed at the leprosy reference center showed much higher antibody titers to all three antigens, while titers of patients from the field were significantly lower. Our results support previous findings that active surveillance by experienced leprologists can diagnose additional cases based on clinical findings, that many would not be identified using ELISA assay with the available biomarkers, and that RLEP qPCR may be used to confirm the majority of the field cases.